Cluster Model Studies of Anion and Molecular Specificities via Electrospray Ionization Photoelectron Spectroscopy - Wang, Xue-Bin (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2017)
Ion specificity, a widely observed macroscopic phenomenon in condensed phases and at interfaces, is a fundamental chemical physics issue. Herein we report our recent studies of such effects using cluster models in an "atom-by-atom" and "molecule-by-molecule" fashion not possible with the condensed-phase methods. We use electrospray ionization (ESI) to generate molecular and ionic clusters to simulate key molecular entities involved in local binding regions and characterize them by employing negative ion photoelectron spectroscopy (NIPES). Inter- and intramolecular interactions and binding configurations are directly obtained as functions of the cluster size and composition, providing molecular-level descriptions and characterization over the local active sites that play crucial roles in determining the solution chemistry and condensed-phase phenomena. The topics covered in this article are relevant to a wide range of research fields from ion specific effects in electrolyte solutions, ion selectivity/recognition in normal functioning of life, to molecular specificity in aerosol particle formation, as well as in rational material design and synthesis.